Perancangan Aplikasi Pemantauan Aktivitas Fisik Mobile Berbasis User-Centered Design - Purbo Pangestu Satria Jati; Susanto Susanto; Titis Handayani (Jurnal Teknologi Informasi dan Multimedia, 2025)
Physical activity monitoring is an important aspect of maintaining health and fitness. With increasing awareness of the importance of a healthy lifestyle, many people are trying to be more physically active. Although many health apps offer physical activity monitoring features, not all apps are designed with user comfort and needs in mind. This study aims to design and evaluate a prototype of a mobile-based health app user interface that emphasizes comfort in physical activity monitoring, using a User-Centered Design (UCD) approach. This approach places the user at the center of the entire design process, ensuring that the design aligns with users' actual preferences and needs. The research methodology includes stages of understanding the user context, identifying user needs, designing the interface (wireframes and user flow), and evaluating the design through A/B testing conducted internally or preliminarily, without involving external respondents. The results of the study indicate that design version B is superior to version A in terms of ease of use and user engagement, as evidenced by a 67.86% increase in interaction and a 71.43% increase in feature usage, based on quantitative metrics such as task completion count and average interaction time measured through internal task scenario simulations. Version B features a more modern appearance and simple, clear navigation. These findings underscore the importance of applying UCD principles in the development of effective and efficient health application interfaces. A better design can encourage user engagement in monitoring physical activity. The application, once designed, not only meets current user needs but also has a strong foundation for future development requirements.